El rol del docente como figura maternante y paternante un factor clave en el desarrollo de la confianza básica en los niños del nivel inicial de la Unidad Educativa Riobamba, cantón Riobamba - Guamán Miranda, Shirley Daniela (2025)
The present research entitled “The role of the teacher as a maternal and paternal figure, a key factor in the development of basic trust in children at the Pre-school Level of the Unidad Educativa Riobamba in Riobamba Canton, Chimborazo Province, aims to determine the impact of the role of teachers at the Pre-school Level 1 and 2 as companions and duplicators of the maternal and paternal functions for the development of basic trust in children. In order to do so, a literature review of a book was carried out, this book was “Un recorrido por el Nivel Inicial desde la Psicología Educacional” by Alejandra Taborda and Beatríz Galende, who analyzed the terms maternal and paternal within the educational context and other classical and contemporary authors. Thus, important data are also collected from the place where the object of study is located and the problem present in this research is registered. On the other hand, an investigation that reflects the influence of the teaching role as a maternal and paternal figure in the development of the basic trust of the children at Pre-school Level is carried out, a survey to the teachers of Pre-school Level to know their perceptions and educational practices regarding the research topic and a workshop that leads to the reflection of such practices. In evaluating this proposal and considering its relevance in the current context, it is concluded that Pre-school teachers have a great influence on the emotional and social development of children, because they see their parental figures reflected in them, this close and affective relationship not only favors the development of the children's basic trust towards their teachers, but also strengthens their self-confidence. Therefore, the influence of teachers goes beyond the academic environment, being a key factor in the process of self- knowledge and emotional development.